Semiclassical Trans-Series from the Perturbative Hopf-Algebraic Dyson-Schwinger Equations: ³ QFT in 6 Dimensions - Borinsky, Michael; Dunne, Gerald V.; Meynig, Max (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
We analyze the asymptotically free massless scalar ³ quantum field theory in 6 dimensions, using resurgent asymptotic analysis to find the trans-series solutions which yield the non-perturbative completion of the divergent perturbative solutions to the Kreimer-Connes Hopf-algebraic Dyson-Schwinger equations for the anomalous dimension. This scalar conformal field theory is asymptotically free and has a real Lipatov instanton. In the Hopf-algebraic approach, we find a trans-series having an intricate Borel singularity structure, with three distinct but resonant non-perturbative terms, each repeated in an infinite series. These expansions are in terms of the renormalized coupling. The resonant structure leads to powers of logarithmic terms at higher levels of the trans-series, analogous to logarithmic terms arising from interactions between instantons and anti-instantons, but arising from a purely perturbative formalism rather than from a semi-classical analysis.